Study of an outbreak of jaundice in Rajshahi, Bangladesh: a sociodemographic and clinical manifestation - Mahi Mubassira; Muntasir Alam Muhib; Syed Abeed-Ul-Haque; Sanzida Khanam; Faruk Hasan (Discover Public Health)
Abstract Background Jaundice symptom outbreaks occur very frequently in Rajshahi, Bangladesh, from January to March 2024. The present study was designed to verify the pattern of jaundice outbreaks and identify the affected population and treatment of jaundice patients. Methods A total of 1151 students living in Rajshahi were tested as samples. Jaundice syndrome was determined by physiological and laboratory tests. Blood and urine samples were tested via an automated clinical chemistry analyzer to confirm the pathophysiology. Moreover, sociodemographic status, food habits and living areas were considered for the patients. Results Among the total number of tested patients, 27.28% and 72.72% were jaundice positive and negative, respectively. In the sociodemographic study, the highest percentage (94%) of jaundice-positive patients were men, which was found in patients aged 20–30 years. In the case of the clinical test, the jaundice-positive patients were hepatitis A virus (HAV)-positive, and the highest average alanine transaminase (ALT) and total bilirubin levels were 1312.67 ± 1.32 U/L and 2.08 ± 0.70 mg/dL, respectively. Conclusion The findings of the present study revealed that the jaundice outbreak was caused by HAV. This study may be helpful for effectively measuring jaundice outbreaks to ensure that safe food and drinking water are urgently needed.